Analysis of The Role of Internal Audit in The Implementation of Corporate Governance at Pt Bank Mandiri - Chalid, Dony Abdul; Rifqi, Achmad (Eduvest - Journal of Universal Studies, 2025)
The need for complex control systems is increasing due to the complexity, size, and operations of companies. To support economic recovery and stable growth in the future, corporate leadership issues have become one of the most important topics of discussion in Indonesia. It is hoped that the principles of corporate governance can improve the quality of financial statements, which will ultimately foster the trust of financial statement users, including investors. With this development of corporate governance, the Board of Directors is forced to improve corporate governance in its own company. As a result, the Council needs help to fulfill its duties. Internal audit is one of the tools that supports this, and its function evolves according to the needs of the company's stakeholders. Business developments result in increased risk, which causes the need to increase. This research will measure the effectiveness of internal audit on corporate governance, and identify the roadmap and Internal Audit Strategic Plan in the form of suggestions and recommendations to improve corporate governance. Data and information collection was obtained through questionnaires, as well as conducting direct interviews with the internal audit department and validating related documents.